Low-Carbon Slag Concrete Design Optimization Method Considering the Coupled Effects of Formwork Stripping, Strength Progress, and Carbonation Durability - Li-Na Zhang; Seung-Jun Kwon; Xiao-Yong Wang (Buildings)
Partially substituting cement with slag is an efficient approach to lowering the carbon footprint of concrete. Earlier research on low-carbon slag concrete has primarily concentrated on the optimization of material strength without considering the coupled effects of formwork stripping time, strength progress, and carbonation durability, which may lead to the risk of steel reinforcement corrosion. To address this limitation, this study introduces an optimized design approach for low-carbon slag concrete that simultaneously accounts for the formwork stripping time and carbonation durability. First, based on strength test results, a strength prediction equation which incorporates the curing age, water-to-(cement+slag) mass ratio, and slag-to-(cement+slag) mass ratio is developed. As such, the coefficients of the equation have clear physical meanings. Both the cement and slag strength coefficients increase with curing age, with the slag strength coefficient exhibiting a greater growth rate than that of cement. Second, an evaluation of concrete’s carbon emissions per 1 MPa increase in strength reveals that, for a given curing age, adopting a low water-to-(cement+slag) mass ratio and a high slag-to-(cement+slag) mass ratio effectively reduces these emissions. Parameter analysis of the carbonation model reveals that increasing the curing time before the onset of carbonation reduces the carbonation depth. Furthermore, four design scenarios are considered in this study: scenario C1 does not consider carbonation durability, with a specified strength of 30 MPa at 28 days; scenario C2 considers carbonation durability, with the same specified strength of 30 MPa at 28 days; scenario C3 does not consider carbonation durability but requires formwork stripping at 7 days; and scenario C4 considers carbonation durability and also requires formwork stripping at 7 days. Through the formulation of constraints for optimization using a genetic algorithm, the appropriate mix proportions for each design scenario are obtained. Finally, the optimization results reveal that, when transitioning from C1 to C2, the actual 28-day concrete compressive strength rises from 30 MPa to 65.139 MPa; when transitioning from C1 to C3, the actual 28-day concrete compressive strength slightly rises from 30 MPa to 30.122 MPa; and when transitioning from C3 to C4, the actual 28-day concrete compressive strength significantly rises from 30.122 MPa to 80.890 MPa. In summary, this study introduces a new approach to the material design of low-carbon slag concrete. In particular, prolonging the curing period plays a crucial role in optimizing low-carbon slag concrete mixtures.